Exploring the association of physical activity on cognitive function in older adults from observational and genetic insights: a combined NHANES and Mendelian randomization study - Liu, Hai-yan; Zhang, Yi-Jing; Zhang, Wen-you (Frontiers in Aging Neuroscience, 2024)
Background: Cognitive function (CF) deterioration is a pressing concern in geriatric research. This study aimed to explore the relationship between physical activity (PA) and CF in older adults.This study adopted a dual approach, employing both observational and genetic approaches through data from the National Health and Nutrition Examination Survey (NHANES) 2011-2014 and Mendelian Randomization (MR) analysis. For the NHANES component, PA levels were evaluated using the Global Physical Activity Questionnaire, and CF was assessed via standardized tests. Multivariate regression, threshold effect analysis, smoothing curve fitting, and subgroup analyses were conducted to examine the association between PA and CF. In parallel, MR methods, using genetic variants as instrumental variables, assessed the causal impact of PA on CF and related conditions such as Alzheimer's disease and dementia.Results: Observational findings from NHANES demonstrated a positive correlation between PA and CF, notably among female participants. The detailed analysis identified specific thresholds of PA that correlate with cognitive enhancements. However, MR results did not support a significant causal relationship between PA and CF or dementia-related outcomes, indicating an absence of a direct genetic basis for the observational associations.Although observational data from NHANES suggest that PA is positively associated with CF in older adults, particularly among women, MR analysis did not confirm these findings as causally related. The discrepancy highlights the complexity of the PA-CF relationship and underscores the need for further research. These results emphasize the potential of PA as a modifiable risk factor for CF, though causal effects remain to be definitively established.